Effect of Debt To Equity Ratio, Firm Size and Sales Growth on Return on Assets In Manufacturing Companies ‘Food and Beverage’ Listed on the Indonesia Stock Exchange (IDX) - Sopandi Sopandi; Rita Yuniarti (PT Mattawang Mediatama Solution, 2023)
This study aims to determine whether there is an effect of debt to equity ratio, firm size and sales growth on return on assets. Researchers used quantitative methods with descriptive and verification approaches as a research method. Secondary data is used as data. The population of this study are 24 food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique uses saturated samples so that a sample of 24 companies is obtained. To measure the effect of the independent variable on the dependent variable, researchers used panel data regression analysis, classical assumption test, goodness of fit test and hypothesis testing. The results of the T test show that the debt to equity ratio has a negative and significant effect on ROA partially. Firm Size has no effect on ROA and Sales Growth has no effect on ROA. The results of the F test show that simultaneously debt to equity ratio, firm size and sales growth have a significant effect on return on assets